810 Preliminary safety, tolerability and efficacy results of KN026 in combination with KN046 in patients with HER2 aberrated solid tumors. (10th December 2020) - Gong, Jifang; Shen, Lin; Dong, Zhi; Liu, Dan; Xu, June; Yang, Jing; Yang, Yue; Qi, Yakun; Men, Jie; Kong, Paul; Xu, Ting
Abstract : Background: HER2 potently inhibits innate immunity through cGAS–STING signaling, 1 Meanwhile HER2 antibody induced ADCP will also lead to macrophage mediated immune suppression. Both preclinical and clinical studies have suggested a coordination of engagement of innate and adaptive immunity with the combination of an anti-HER2 antibody and an immune checkpoint blockade. KN026 is a novel bispecific antibody that simultaneously binds to two distinct HER2 epitopes. KN046 is a novel bispecific antibody that blocks both PD-L1 interaction with PD-1/CD80 and CTLA-4 interaction with CD80/CD86. Here we reported the interim results from an ongoing phase Ib dose escalation and expansion study assessing the safety, tolerability and preliminary efficacy for KN026 in combination with KN046 in Patients with HER2 aberrated solid tumors. Methods: This study enrolled pts with solid tumors who failed available standard of care, HER2 aberration status confirmed locally (HER2 mutation, HER2 amplification and/or HER2 overexpression). Eligible pts received combination of KN026 and KN046 at three dose levels until disease progression, unacceptable toxicity or withdrawal of informed consent (DL1: KN026 20 mg/kg Q2W + KN046 3 mg/kg Q2W; DL2: KN026 20 mg/kg Q2W with loading on Days 1, 8 of Cycle 1 + KN046 5 mg/kg Q3W; DL3: KN026 30 mg/kg Q3W with loading on Days 1, 8 of Cycle 1 + KN046 5 mg/kg Q3W). Tumor response was evaluated Q8W per RECIST 1.1. Primary endpoint was DLT and key secondary endpoints were efficacy parameters (ORR, DOR, PFS). Results: As of the Sep. 08, 2020, 25 pts were enrolled into DL1 (n = 20, 3 for dose escalation), DL2 (n = 3) and DL3 (n = 2) (mGC/GEJ 15 pts; mCRC 8 pts; other solid tumors 2 pts). 15 pts remained on the study treatment and 10 pts discontinued treatment due to disease progression (n=5), death (n=2) and other reasons (n=3). 18 pts had HER2-positive status (12 of 18 failed previous trastuzumab therapy), 2 pts had HER2 mutation and 5 pts had HER2 low expression (without FISH amplification). No DLTs were observed. No pts experienced LVEF decreased or other clinically meaningful cardiac AEs. Treatment-related TEAEs occurred in 23 (92%) pts, of which 6 (24%) pts experienced grade 3 or above treatment-related TEAEs. 11 (44%) pts experienced irAEs, majority were of grade 1 or 2 except that 1 patient experienced grade 3 immune-mediated endocrinopathy. The most common (frequency ≥ 15%) KN026 or KN046 related TEAEs were infusion related reaction (n=11, 44.0%), anaemia (n=9, 36.0%), white blood cell count decreased (n=6, 24.0%), diarrhea (n=5, 20.0%), AST increased (n=5, 20.0%), platelet count decreased (n=5, 20.0%), rash (n=5, 20.0%) and ALT increased (n=4, 16.0%). The objective response rate in pts with HER2-positive tumors (n = 14 efficacy evaluable pts) was 9/14 (64.3%, 95% CI 35.1~87.2%) and disease control rate 13/14 (92.9%, 95% CI 66.1~99.8%). 4 out of 5 pts with HER2 mutation or low expression achieved SD including one patient with SD for more than 24 weeks. 2 death cases due to disease progression were reported, both only received one cycle of KN026 plus KN046 due to COVID-19 restriction. Conclusions: KN026 combined with KN046 is well tolerated and has demonstrated preliminary albeit profound anti-tumor activity in HER2-positive solid tumors. Trial Registration: Clinical trial information: NCT04040699 Reference: Shiying Wu, Qian Zhang, Fei Zhang, et al. HER2 recruits AKT1 to disrupt STING signalling and suppress antiviral defence and antitumour immunity. Nature Cell Biology 2019;21 :1027–1040.